Abundance of Ordo Lepidoptera in The Land Conversion of Ciwidey Pine Forest - Sabella Friska S. Mulyono; Suhara Suhara; Iwan Setia Kurniawan (Al-Hayat: Journal of Biology and Applied Biology, 2022)
The study entitled "Abundance of Ordo Lepidoptera in The Land Conversion of Ciwidey Pine Forest" aims to obtain the information about the abundance of insects of the ordo Lepidoptera and the influence of climatic factors on the abundance. The research method used is descriptive method, the research design is belt transect, and the sampling techniques used are pitfall trap, hand sorting, beating tray, and insect net. There are 6 stations with 5 quadrants in each. The results of this study obtained 37 individuals from 10 species, 10 genus, and 6 families. Abundance at station one is worth of 2 individuals/m2, abundance at station two is worth of 4 individuals/m2, abundance at station three is worth of 6 individuals/m2, abundance at station four is worth of 6 individuals/m2, abundance at station five is worth of 2 individuals/m2, abundance at station six worth of 10 individuals/m2.